Pearl lines - Walter Price - Wesseler, Moritz 1980- (Kölnischer Kunstverein, 2019)
With a focus on both older and newer works, and complemented by site-specific wall paintings and drawings, 'Pearl Lines' presents the colorful and surreal paintings of New York based artist Walter Price (born 1989). It is published for his exhibition at Kölnischer Kunstverein. Exhibition: Kölnischer Kunstverein, Cologne, Germany (20.04. - 17.06.2018)
Impressum: Published on the occasion of the exhibition at Kölnischer Kunstverein, Cologne, Germany, April 20-June 17, 2018
Edition of 1000. Special hardcover edition of 50
Keywords: Price, Walter -- 1989-; Price, Walter / 1989- / Exhibitions; Exhibition catalogs; Ausstellungskatalog -- Kölnischer Kunstverein -- 20.04.2018-17.06.2018 -- Köln; Bildband